PHYSICO-CHEMICAL PROPERTIES OF BRICK KILN DUST AMENDED SOILS AND THEIR EFFECT ON SOLANUM TUBEROSUM - Tomar, Deepali; Khan, Abrar A. (Ecoprint: An International Journal of Ecology, 2013)
The study was conducted to analyze the physico-chemical properties of various levels of brick kiln dust in soil application (0, 5, 10, 15, 20, 25, 30, 40 and 50%), before planting and after harvesting of potato (Solanum tuberosum) crop and to observe their impact on various parameters of potato plant. The pH, EC, CEC, WHC, pore space, sulphate, chloride, phosphorus, magnesium, zinc, manganese and boron increased at all the levels of brick kiln dust, while, nitrogen and potassium decreased at all the levels before planting of potato crop. After harvesting of potato crop all physico-chemical properties were still greater than control but less than pre-planting of potato, except P and Mg which decreased gradually upto 30%; and K as well as Mn upto 40%, and then they increased in subsequent levels. While N was recorded only in control and at 50% treatment. Application of brick kiln dust in soil from 5% to 40% was found beneficial for plant growth, yield, biomass, photosynthetic pigments, carbohydrate contents, and phosphorus and potassium concentrations of plants and the highest increase in above parameters was recorded at 25% level. At 50% level, there was marked reduction in all these parameters. However, nitrogen concentration of plants and protein content in tubers decreased gradually as levels of kiln dust were increased. DOI: http://dx.doi.org/10.3126/eco.v18i0.9394 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: Uploaded date: 12/20/2013